2018
DOI: 10.1186/s40478-018-0570-9
|View full text |Cite
|
Sign up to set email alerts
|

Medulloblastoma therapy generates risk of a poorly-prognostic H3 wild-type subgroup of diffuse intrinsic pontine glioma: a report from the International DIPG Registry

Abstract: With improved survivorship in medulloblastoma, there has been an increasing incidence of late complications. To date, no studies have specifically addressed the risk of radiation-associated diffuse intrinsic pontine glioma (DIPG) in medulloblastoma survivors. Query of the International DIPG Registry identified six cases of DIPG with a history of medulloblastoma treated with radiotherapy. All patients underwent central radiologic review that confirmed a diagnosis of DIPG. Six additional cases were identified in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
22
1
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(32 citation statements)
references
References 46 publications
(69 reference statements)
8
22
1
1
Order By: Relevance
“…One TIHGG case in our series clustered with diffuse midline glioma (DMG) but lacked the defining H3K27M mutation (Case 13). One recent case series described three patients who had received prior radiotherapy for medulloblastoma and later developed tumors clinically consistent with DMG 19 . While one case in our series had the H3K27M mutation (Case 7), this case lacked methylation data and was not be able to be clustered against reference cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…One TIHGG case in our series clustered with diffuse midline glioma (DMG) but lacked the defining H3K27M mutation (Case 13). One recent case series described three patients who had received prior radiotherapy for medulloblastoma and later developed tumors clinically consistent with DMG 19 . While one case in our series had the H3K27M mutation (Case 7), this case lacked methylation data and was not be able to be clustered against reference cohorts.…”
Section: Discussionmentioning
confidence: 99%
“…Previous literature has shown that medulloblastomas can either originate in the brainstem or directly invade the brainstem, which can cause the misdiagnosis of medulloblastoma as brainstem glioma 1,3,4 . Brainstem lesions have been found in post‐radiotherapy medulloblastoma patients, which can cause uncertainty regarding whether to diagnose the lesions as medulloblastoma recurrence or as new brainstem gliomas 5,6 . These pathologies require different treatment regimens and prognoses.…”
Section: Introductionmentioning
confidence: 99%
“…These pathologies require different treatment regimens and prognoses. Thus, the differentiation between these two types of tumors is essential for precise therapeutic strategy planning and improved treatment outcomes 1‐6 …”
Section: Introductionmentioning
confidence: 99%
“…Gliomas can occur as primary brain tumours but may also arise as a consequence of radiation therapy in survivors of other paediatric brain tumours, such as medulloblastoma or ependymoma. Radiation-induced gliomas (RIGs) are at least as, if not more, aggressive than spontaneously occurring gliomas [ 7 , 8 , 9 ], and are invariably fatal, with a cumulative incidence ranging from 0.3% to 3.96% following radiation treatment for paediatric brain tumours [ 8 , 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies investigating molecular alterations in paediatric RIGs are few and report small numbers of patient samples. These studies suggest that paediatric RIGs demonstrate more overlap with pilocytic astrocytomas (PAs) [ 7 ] and adult primary GBMs [ 8 ] than with paediatric high-grade gliomas. Overexpression of ERBB3, SOX10 and PDGFRA has been reported in paediatric RIG [ 7 , 14 ], as well as mutations in TP53 , PDGFRA and PIK3CA , homozygous deletion of CDKN2A and MTAP , and alterations in multiple receptor tyrosine kinase and Ras-Raf-MAPK genes [ 8 , 14 , 16 , 17 , 18 , 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%